2019
DOI: 10.3390/ijms20051116
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of DNA Topoisomerase I on T3SS Activity, Antibiotic Susceptibility and Quorum- Sensing-Independent Pyocyanin Synthesis in Pseudomonas aeruginosa

Abstract: Topoisomerases are required for alleviating supercoiling of DNA during transcription and replication. Recent evidence suggests that supercoiling of bacterial DNA can affect bacterial pathogenicity. To understand the potential regulatory role of a topoisomerase I (TopA) in Pseudomonas aeruginosa, we investigated a previously isolated topA mutation using genetic approaches. We here report the effects of the altered topoisomerase in P. aeruginosa on type III secretion system, antibiotic susceptibility, biofilm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
(130 reference statements)
2
5
0
Order By: Relevance
“…Moreover, SCN was the compound causing the highest reduction in the viability and adhesion of sessile bacteria, decreasing biofilm thickness and the size of monolayers. Recent studies in Pseudomonas aeruginosa support the relationship established in our study between TopoI and the formation of biofilms [62]. It has also been described the anti-biofilm effect of other alkaloid, based on the inhibition of effective adhesion and growth of bacteria forming the biofilm [63].…”
Section: Plos Onesupporting
confidence: 84%
“…Moreover, SCN was the compound causing the highest reduction in the viability and adhesion of sessile bacteria, decreasing biofilm thickness and the size of monolayers. Recent studies in Pseudomonas aeruginosa support the relationship established in our study between TopoI and the formation of biofilms [62]. It has also been described the anti-biofilm effect of other alkaloid, based on the inhibition of effective adhesion and growth of bacteria forming the biofilm [63].…”
Section: Plos Onesupporting
confidence: 84%
“…50 Previous studies have shown that the QS system of PA is often directly regulated by transcriptional regulators. [51][52][53] According to our result, we speculate that PtrA may directly act on the QS system of PA. However, which system PtrA mainly acts on and how it affects the interaction of each system needs to be further explored in our subsequent research.…”
Section: Discussionsupporting
confidence: 60%
“…As bacterial topoisomerase IA is essential for cellular viability of a number of important bacterial pathogens, this enzyme also represents a valid target for novel antibiotics aimed at overcoming antimicrobial resistance [6]. Again, CM3 was the best inhibitor (Table 2).…”
Section: Resultsmentioning
confidence: 99%